2016
DOI: 10.3892/or.2016.4797
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-195 promotes prostate cancer progression by targeting HMGA1

Abstract: Abstract. Aberrant deregulation of is associated with tumorigenesis and the development of cancer. However, its expression and function in prostate cancer (PCa) remain to be elucidated. In the present study, we found that miR-195 expression levels were decreased in human PCa samples and were correlated with patient prognosis. miR-195 overexpression inhibited cell proliferation, cell cycle progression and tumorigenesis via directly targeting HMGA1. Downregulation of HMGA1 expression had an effect similar to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 29 publications
3
27
0
1
Order By: Relevance
“…In striking contrast, endometrial cancer tissue samples showed a significant decrease in fourteen tumor-suppressive miRNAs (Figure 1C). It is of interest to note here that all of the fourteen downregulated miRNAs, namely, miR-26a-5p [22, 23], miR-150-5p [24, 25], let-7f-5p [26, 27], miR-26b-5p [22, 23, 28], let-7c-5p [26, 27], miR-23b-5p [29-31], miR-126-3p [32], miR-125b-5p [33], hsa-miR-195-5p [34, 35], miR-424-5p [36, 37], hsa-miR-374a-5p [38-40], let-7a-5p [26, 27] , let-7e-5p [26, 27], and miR-125a-5p [41, 42] are known to have tumor-suppressive function in many cancers. Taken together with the upregulated genes, our results identify a panel of miRNAs that correlates with the tumor phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…In striking contrast, endometrial cancer tissue samples showed a significant decrease in fourteen tumor-suppressive miRNAs (Figure 1C). It is of interest to note here that all of the fourteen downregulated miRNAs, namely, miR-26a-5p [22, 23], miR-150-5p [24, 25], let-7f-5p [26, 27], miR-26b-5p [22, 23, 28], let-7c-5p [26, 27], miR-23b-5p [29-31], miR-126-3p [32], miR-125b-5p [33], hsa-miR-195-5p [34, 35], miR-424-5p [36, 37], hsa-miR-374a-5p [38-40], let-7a-5p [26, 27] , let-7e-5p [26, 27], and miR-125a-5p [41, 42] are known to have tumor-suppressive function in many cancers. Taken together with the upregulated genes, our results identify a panel of miRNAs that correlates with the tumor phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…HMGA1 is primarily expressed in fetal tissues (Hynes et al, 1994) and many cancer tissues, such as colorectal cancer (Williama et al, ), breast cancer (Cianfrocca et al, ), pancreatic cancer (Piscuoglio et al, ), ovarian cancer (Liu et al, ), and prostate cancer (Zhang et al, ). In this study, we found that HMGA1 expression in breast cancer tissues was stronger than that in normal breast tissues, which is consistent with the previous reports on breast cancer cell lines and breast cancer tissues (Liu et al, ; Sepe et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…High mobility group A1 (HMGA1), a member of the HMGA family, is highly expressed during embryogenesis (Pegoraro et al, ), while HMGA1 protein expression levels are low or undetectable in normal adult tissues (Zhou et al, ; van't Veer et al, ). Studies have shown that HMGA1 plays an important role in several types of cancers, such as breast cancer (Cianfrocca et al, ), colorectal cancer (Williama et al, ), pancreatic cancer (Piscuoglio et al, ), prostate cancer (Zhang et al, ), ovarian cancer (Liu et al, ), and lung cancer (Lin et al, ). Furthermore, some studies have reported that HMGA1 is highly expressed in human breast cancer tissues, and the overexpression of HMGA1 is associated with breast cancer progression (Huang et al, ).…”
mentioning
confidence: 99%
“…miR-195 inhibited the tumor angiogenesis and growth by suppressing IRS1 in breast cancer [17]. In prostate cancer cells, miR-195 functions as a tumor suppressor gene by suppressing HMGA1 [30]. In esophageal squamous cell carcinoma cells, Fu et al manifested that miR-195 downregulation inhibited cell proliferation and invasion by targeting Cdc42 [16].…”
Section: Discussionmentioning
confidence: 99%